7 Tesla Chlorine (35Cl) and Sodium (23Na) MR Imaging of an Enchondroma - Weber, Marc-André; Seyler, Lisa; Nagel, Armin M. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2021)
We demonstrated the feasibility of 7 Tesla sodium (23Na) and chlorine (35Cl) MRI of a solitary enchondroma. For this, we established dedicated sequences on a 7-Tesla whole-body system with the following key parameters for 35Cl MRI: TE/TR = 0.35/60 ms, TRO = 5 ms, α = 90°, Δx3 = (6 mm)3, 3 averages, Tacq = 30 min and for 23Na MRI: TE/TR = 0.4/101 ms, TRO = 10ms; α = 90°; Δx3 = (1.9 mm)3, 3 averages, Tacq = 30 min 18 s. The measured apparent Na+ concentration was 255 mmol/l and was approximately 7-fold higher than the apparent Cl– concentration with about 36 mmol/l. Additionally, repeated proton MRI examinations demonstrated constant but subtle growth (≈ 0.65 ml/year) over 14 years. In conclusion, enchondromas obviously have a high contrast-to-noise ratio when compared with the normal bone marrow in 23Na and 35Cl MRI, which may contribute to detection and differentiation in unclear or subtle cases.Key Points:Citation Format